Limitations on the ability to negotiate justice: attorney perspectives on guilt, innocence, and legal advice in the current plea system - Helm, Rebecca K. (Psychology, crime & law, 2018)
In the American criminal justice system the vast majority of criminal convictions occur as the result of guilty pleas, often made as a result of plea bargains, rather than jury trials. The incentives offered in exchange for guilty pleas mean that both innocent and guilty defendants plead guilty. We investigate the role of attorneys in this context, through interviews with criminal defense attorneys. We examine defense attorney perspectives on the extent to which innocent defendants are (and should be) pleading guilty in the current legal framework and investigate their views of their own role in this complex system. We also use a hypothetical case to probe the ways in which defense attorneys consider guilt or innocence when providing advice on pleas. Results indicate that attorney advice is influenced by guilt or innocence, but also that attorneys are limited in the extent to which they can negotiate justice for their clients in a system in which uncertainty and large discrepancies between outcomes of guilty pleas and conviction at trial can make it a sensible option to plead guilty even when innocent. Results also suggest conflicting opinions over the role of the attorney in the plea-bargaining process.